The ASAS-SN catalogue of variable stars VI: an all-sky sample of δ Scuti stars. Issue 3 (19th February 2020) - Jayasinghe, T; Stanek, K Z; Kochanek, C S; Vallely, P J; Shappee, B J; Holoien, T W-S; Thompson, Todd A; Prieto, J L; Pejcha, O; Fausnaugh, M; Otero, S; Hurst, N; et al.
ABSTRACT: We characterize an all-sky catalogue of ∼8400 δ Scuti variables in ASAS-SN, which includes ∼3300 new discoveries. Using distances from Gaia DR2, we derive period–luminosity relationships for both the fundamental mode and overtone pulsators in the WJK, V, Gaia DR2 G, J, H, Ks, and W 1 bands. We find that the overtone pulsators have a dominant overtone mode, with many sources pulsating in the second overtone or higher order modes. The fundamental mode pulsators have metallicity-dependent periods, with log10 ( P ) ∼ −1.1 for [Fe/H]-0.3 and log10 ( P ) ∼ −0.9 for [Fe/H]0, which leads to a period-dependent scale height. Stars with P0.100 d are predominantly located close to the Galactic disc (| Z|0.5 kpc ). The median period at a scale height of Z0 kpc also increases with the Galactocentric radius R, from log10 ( P ) ∼ −0.94 for sources with R9 kpc to log10 ( P ) ∼ −0.85 for sources with R7 kpc, which is indicative of a radial metallicity gradient. To illustrate potential applications of this all-sky catalogue, we obtained 30 min cadence, image subtraction TESS light curves for a sample of 10 fundamental mode and 10 overtone δ Scuti stars discovered by ASAS-SN. From this sample, we identified two new δ Scuti eclipsing binaries, ASASSN-V J071855.62−434247.3 and ASASSN-V J170344.20−615941.2 with short orbital periods of P orb = 2.6096 and 2.5347 d, respectively.